问题
解答题
计算: (1)8+(-
(2)-82+72÷36 (3)7
(4)25×
(5)(-79)÷2
(6)(-1)3-(1-
(7)2(x-3)-3(-x+1) (8)-a+2(a-1)-(3a+5) |
答案
(1)8+(-
)-5-(-0.25)1 4
=(8-5)+(-0.25+0.25)
=3+0
=3;
(2)-82+72÷36
=-82+2
=-80;
(3)7
×11 2
÷(-9+19)3 4
=
×15 2
÷107 4
=
;21 16
(4)25×
+(-25)×3 4
+25×(-1 2
)1 4
=25×(
-3 4
-1 2
)1 4
=25×0
=0;
(5)(-79)÷2
+1 4
×(-29)4 9
=-79×
+4 9
×(-29)4 9
=(-79-29)×4 9
=-108×4 9
=-48;
(6)(-1)3-(1-
)÷3×[3-(-3)2]1 2
=-1-
÷3×[3-9]1 2
=-1-
÷3×[-6]1 2
=-1+1
=0;
(7)2(x-3)-3(-x+1)
=2x-6+3x-3
=5x-9;
(8)-a+2(a-1)-(3a+5)
=-a+2a-2-3a-5
=-2a-7.